Long-Run Effects of the Accelerated Cost Recovery System - Fullerton, Don; Henderson, Yolanda Kodrzycki (The Review of Economics and Statistics, 1985)
This paper represents part of a larger ongoing project to build and use a numerical general equilibrium model of the U.S. tax system. Charles Ballard,